Workforce Design And Employee Workload Using The Full-Time Equivalent Method At PT XZY - Amri Amri (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
One of the factors that affect employee performance is workload. If employees are given too much work, problems will arise. For example, some representatives have too high responsibilities ( overloaded ), while other workers have small responsibilities ( underloaded ). This kind of problem also occurs at PT. XZY, Â so it is essential to research the status of responsibility, which can then be used to design the Number of employees. The workload of each station is calculated using the Full Time Equivalent (FTE) method, which converts workload hours into the Number of people needed to complete a particular task. From the results of the review, it was found that there were deviations in responsibility at five workstations where three stations had overloaded workloads or values between 1.28 found at the wedding, cutting, and packing stations. A further two stations have standard work with values 1-1.28 found at co-gas filling stations and packaging and vacuum. The findings show that 18 employees are the ideal workforce. Changing the composition of the Number of workers according to the calculation of the optimal Number of workers can improve employee performance. The manuscript should contain an abstract. The abstract should be self-contained and citation-free and should not exceed 250 words. The abstract should state the work's purpose, approach, results, and conclusions. The author should assume that the reader has some knowledge of the subject but has not read the paper. Thus, the abstract should be intelligible and complete (no numerical references); it should not cite figures, tables, or sections of the paper. The abstract should be written using the third person instead of the first person.